Research progress of 3D printing combined with thermoplastic foaming - Sun, Bin; Wu, Lixin (Frontiers in Materials, 2022)
Thermoplastic foam additive manufacturing is a brand-new industry that perfectly combines the advantages of polymer foaming with AM. The 3D printing industry currently suffers from limited available materials and monolithic part manufacturing, and 3D printed foam offers a new way of thinking to address these challenges. Designing multifunctional components with additive manufacturing gives designers great flexibility, while foaming reduces the weight of materials and costs. The combination of the two allows for the creation of lightweight structural and functional items with differentiated physical properties. This one-of-a-kind and innovative approach can be achieved in the printed section. 3D printing foam, on the other hand, is still in its infancy. This review examines the respective functions and applications of additive manufacturing and foaming, and then attempts to summarize four commonly used 3D printing methods at this stage:1) cellular scaffolds; 2) composite printing foam; 3) post-foaming of printed solid scaffolds; 4) in-situ foam 3D printing. Among these methods, in-situ foam 3D printing is the technique that properly merges the foaming and fused filament fabrication processes. Although in the early stages of research and not yet fully established, this foam 3D printing technique seems to be the trend to replace other foaming processes.